Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1399-3054.2008.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Stronger induction of callose deposition in barley by Russian wheat aphid than bird cherry‐oat aphid is not associated with differences in callose synthase or β‐1,3‐glucanase transcript abundance

Abstract: The effects of infestation by the bird cherry-oat aphid (BCA), (Rhopalosiphum padi L) and the Russian wheat aphid (RWA) (Diuraphis noxia Mordvilko) on callose deposition and transcription of genes related to callose accumulation were investigated in barley (Hordeum vulgare L. cv. Clipper). The BCA, which gives no visible symptoms, induced very limited callose deposition, even after 14 days of infestation. In contrast, RWA, which causes chlorosis, white and yellow streaking and leaf rolling, induced callose acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
(53 reference statements)
3
36
3
Order By: Relevance
“…This is because deposition of wound callose becomes noticeable within longitudinal veins, only after 14 d of feeding when the starting small colony (5 aphids) had grown to about 70 aphids (Saheed et al, 2007a). This was in agreement with our earlier observation even when the starting aphid population was ten (Saheed et al, 2009). The callose deposition thereafter increases until the end of the experiments-21d ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is because deposition of wound callose becomes noticeable within longitudinal veins, only after 14 d of feeding when the starting small colony (5 aphids) had grown to about 70 aphids (Saheed et al, 2007a). This was in agreement with our earlier observation even when the starting aphid population was ten (Saheed et al, 2009). The callose deposition thereafter increases until the end of the experiments-21d ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Diuraphis noxia (Russian wheat aphid, RWA) induce rapid wounding and severe symptoms such as chlorosis, necrosis and leaf rolling, which may appear on its host even with a single aphid infestation (Walters et al, 1980;Saheed et al, 2007a, b). In contrast, small populations of Rhopalosiphum padi (bird cherry-oat aphid, BCA) do not induce rapid visible damage symptoms or wound callose (Messina et al, 2002;Saheed et al, 2007a;2009). However, an increase in the BCA population size has been shown to results in the development of golden yellow streak symptoms in host plants (Agronomy guide 2002;UCIPM 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of b-1,3-glucanases may be involved in the breakdown of induced callose (Hao et al 2008). Our earlier studies have indicated that there was very little buildup of callose after infestation by bird cherry-oat aphid in a susceptible barley cultivar (Saheed et al 2009). Callose was to a much stronger level induced by infestation by RWA, which however also caused much stronger induction of b-1,3-glucanases (among them 1637_s_at and 1636_s).…”
Section: Discussionmentioning
confidence: 95%
“…Callose was to a much stronger level induced by infestation by RWA, which however also caused much stronger induction of b-1,3-glucanases (among them 1637_s_at and 1636_s). These results were taken to suggest that the differences between RWA and bird cherry-oat aphid in causing callose were not likely to be caused by different levels of b-1,3-glucanases (Saheed et al 2009). Still we cannot exclude the possibility that b-1,3-glucanases are instrumental in preventing callose accumulation as a response to bird cherry-oat aphid and thereby increasing susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…For example, 4MOI3M, and its catabolism by myrosinase PEN2, is essential to the Arabidopsis callose deposition response to pathogens (Clay et al, 2009). Callose deposition might similarly mediate resistance to dodder, as it has been shown to be induced by other plant antagonists that penetrate cells and/or feed on phloem, including various pathogens, aphids, whiteflies, and the parasitic plant Orobanche crenata (de Luque and Lozano, 2007;Kempema et al, 2007;Clay et al, 2009;Saheed et al, 2009). In any event, while the specific role of indole glucosinolates in parasite-host interactions remains to be clarified, their induction by dodder infestation, together with the observed effects of atr1D and cyp79B2/B3 on dodder performance, strongly suggests that these compounds, which are known to be involved in defense against herbivores and pathogens, also play a role in resistance to parasitic plants.…”
Section: Dodder Growth Is Enhanced On Glucosinolate-free Hostsmentioning
confidence: 99%